Keynote Speech. The nexus of climate change, agrobiodiversity and nutrition: Implications on mental health - Ekesa, Beatrice (2023)
Agrobiodiversity provides us with a diverse basket of nutritious foods, increases the self-sustainability and resilience of the ecosystem. The changes in climatic/weather conditions that have been recorded in the last century especially the rise in temperatures, have resulted to changes in precipitation patterns, the rise of sea levels, higher incidence of extreme weather events and the increase of greenhouse gases – especially carbon dioxide – in the atmosphere. In addition to resulting into floods, wild wires and droughts, these changes have had a significant effect on agrobiodiversity.